Investigations of the hydration of polyethyleneglycols using an acoustic method - JUSZKIEWICZ, Adam; POTACZEK, Jadwiga (Archives of Acoustics, 1977)
Measurements of the velocity of ultrasound in alcohol — water solutions of polyethylene glycols with molecular weights 400, 1500, 2000, 15000 and 20000 at a temperature of 25 ± 0.1°C have been made and the values of the hydration numbers defined by the YASUNAGA method.